Tax knowledge, persepsi keadilan sistem perpajakan, dan integritas pemerintah: Determinan tax morale mahasiswa Jurusan Akuntansi Universitas Sam Ratulangi - Angel Gloria Gracia Mocodompis; Robert Lambey; Christian Datu (Manajemen Bisnis dan Keuangan Korporat, 2026)
Taxes are the backbone of financing crucial sectors such as education, health, infrastructure, and social protection, yet voluntary compliance remains heavily shaped by taxpayers' internal motivation, or tax morale. This study examines the partial effects of tax knowledge, perceived fairness of the tax system, and government integrity on the tax morale of potential taxpayers, with a focus on accounting students at Sam Ratulangi University, Manado. Using a quantitative approach, primary data were collected through an online questionnaire distributed to 281 accounting students from the 2021–2023 cohorts, selected via proportionate stratified random sampling. The data were analyzed using multiple linear regression with SPSS 29, supported by validity, reliability, and classical assumption tests. The results show that tax knowledge and perceived fairness of the tax system have a positive and significant effect on tax morale, whereas government integrity has a negative and significant effect. Simultaneously, the three variables significantly influence tax morale, explaining 80.2% of its variation. The negative effect of government integrity suggests that critical, educated young taxpayers hold high expectations of transparency and accountability; when perceived government conduct falls short of these expectations, their willingness to comply voluntarily weakens. These findings, interpreted through the Theory of Planned Behavior, underscore the importance of strengthening tax education, ensuring a fair tax system, and improving government transparency to nurture the tax morale of future taxpayers.